Influence of Speed and Land Slope on uniformity of distribution and metering of Cowpea seeds - SAQIB , G. S.; SEGUN, O. O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Investigations were carried out to evaluate the effects of field slope and forward speed on the metering uniformity of the grain drills for planting cowpea. The study was conducted in the laboratory using a John Decre model 8250 grain drill while the field slopes and forward speeds were simulated. The field slopes were varied from zero to 12.5 degrees, while the forward speeds were varied from 3 to 6 km/h. The metering uniformity of the drill was measured in terms of coefficient of variation in the seeds metered and delivered by various seed delivery tubes across the width of the machine. The actual seeding rate delivered by the grain drill under various field and operating conditions was also determined. Results indicated that the field slope and forward speed had significant effect (p <0.01) on the metering uniformity and seeding rate. There was decrease in the metering uniformity and the seeding rate with an increase in the field slope in the range tested. Similarly, an increase in forward speed resulted in poorer metering uniformity and lesser seeding rate at the field slopes ranging from zero to 12.5 degrees. The interaction between the filed slope and the forward speed appeared to be non-significant. Statistical models were developed to predict the metering uniformity and the seeding rate delivered by a grain drill operating at various forward speeds for planting cowpea seeds in sloping lands of Oyo State of Nigeria.